Nutrient limitation is the main regulatory factor for carotenoid accumulation and for Psy and Pds steady state transcript levels in Dunaliella salina (Chlorophyta) exposed to high light and salt stress - Coesel, Sacha (2014)
Dunaliella salina (Dunal) Teodoresco (1905) is a green unicellular alga able to withstand severe salt, light, and nutrient stress, adaptations necessary to grow in harsh environments such as salt ponds. In response to such growth conditions, this microalga accumulates high amounts of β-carotene in its single chloroplast. In this study, we show that carotenoid accumulation is consistently inhibited in cells grown in nutrient-supplemented media and exposed either to high-light or medium-low-light conditions. Likewise, carotenogenesis in cells shifted to higher salinity (up to 27% NaCl) under medium-low-light conditions is inhibited by the presence of nutrients. The steady-state levels of transcripts encoding phytoene syn- thase and phytoene desaturase increased substantially in D. salina cells shifted to high light or high salt under nutrient- limiting conditions, whereas the presence of nutrients inhibited this response. The regulatory effect of nutrient availability on the accumulation of carotenoids and mes- senger RNA levels of the first two enzymes committed to carotenoid biosynthesis is discussed.